Sustainable Operations Management Practices: A Comparative Study of Manufacturing Industries - Mohammad Chaidir; Dadang Irawan; Seger Santoso (International Journal of Management, Accounting & Finance (KBIJMAF), 2024)
This study presents a comparative analysis of sustainable operations management practices across manufacturing industries. In an era marked by growing environmental concerns and resource constraints, the adoption of sustainable practices in manufacturing has become imperative. Through a comprehensive review of literature and empirical data gathered from multiple manufacturing sectors, this research examines various dimensions of sustainable operations management, including environmental sustainability, social responsibility, and economic viability. By employing a comparative framework, the study identifies common trends, challenges, and best practices in sustainable operations management among diverse manufacturing sectors. The findings underscore the significance of integrating sustainability principles into operational strategies to enhance competitiveness, mitigate environmental impacts, and foster long-term value creation. Moreover, the study highlights the role of technological innovation, regulatory frameworks, and stakeholder collaboration in promoting sustainable practices across manufacturing industries. The insights generated from this research contribute to the advancement of knowledge in sustainable operations management and offer practical implications for policymakers, industry practitioners, and academia striving towards a more sustainable future.